2021
DOI: 10.5194/esurf-2021-72
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Signal response of the Swiss plate geophone monitoring system impacted by bedload particles with different transport modes

Abstract: Abstract. Controlled experiments were performed to investigate the acoustic signal response of the Swiss plate geophone (SPG) system impacted by bedload particles varying in size, impact angle and transport mode. The impacts of bedload particles moving by saltation, rolling, and sliding were determined by analyzing the experimental videos and corresponding vibration signals. For a particle impact on the bed or on the geophone plates, the signature of the generated signal in terms of maximum amplitude, number o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…A decrease in with increasing particle size was observed for different bedload surrogate monitoring techniques (Belleudy et al, 2010;Uher and Benes, 2012;Barrière et al, 2015). Furthermore, has the advantage of showing weaker dependency on the flow velocity and transport mode than the maximum registered packet amplitude (Wyss et al 2016b;Chen et al, 2021). As shown by Nicollier et al (2021b), also contains information about the impact location of a packettriggering particle.…”
Section: Centroid Frequencymentioning
confidence: 99%
See 2 more Smart Citations
“…A decrease in with increasing particle size was observed for different bedload surrogate monitoring techniques (Belleudy et al, 2010;Uher and Benes, 2012;Barrière et al, 2015). Furthermore, has the advantage of showing weaker dependency on the flow velocity and transport mode than the maximum registered packet amplitude (Wyss et al 2016b;Chen et al, 2021). As shown by Nicollier et al (2021b), also contains information about the impact location of a packettriggering particle.…”
Section: Centroid Frequencymentioning
confidence: 99%
“…increases together with the transport rate, with the transport of large particles (which typically generate packets of longer durations), and with the occurrence of sliding and rolling particles (Chen et al, 2021). The long packets take the place of multiple shorter packets that would otherwise be individually counted; thus, they lead to underestimated mass fluxes for a given value.…”
Section: Transport Ratementioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in f centroid with increasing particle size was observed for different bedload surrogate monitoring techniques (Belleudy et al, 2010;Uher and Benes, 2012;Barrière et al, 2015). Furthermore, f centroid has the advantage of showing weaker dependency on the flow velocity and transport mode than the maximum registered packet amplitude (Wyss et al 2016b;Chen et al, 2022). As shown by Nicollier et al (2022), f centroid also contains information about the impact location of a packet-triggering particle.…”
Section: Centroid Frequencymentioning
confidence: 96%
“…Numerous studies have reported successful calibration of impact plate systems in laboratory flumes (e.g., Bogen and Møen, 2003;Krein et al, 2008;Tsakiris et al, 2014;Mao et al, 2016;Wyss et al, 2016b, c;Kuhnle et al, 2017;Chen et al, 2022), although transferring these flume-based calibrations to the field remains challenging. Nonetheless, flume experiments are valuable because they allow systematically exploring relationships between the recorded signal, the transport rates of different sediment size fractions, and the hydraulic conditions.…”
Section: Introductionmentioning
confidence: 99%